Atomic Insights of Self‐Healing in Silicon Nanowires (Adv. Funct. Mater. 6/2023). (2nd February 2023) - Cui, Junfeng; Sun, Yang; Chen, Huixin; Yang, Yingying; Chen, Guoxin; Ke, Peiling; Nishimura, Kazuhito; Yang, Yong; Tang, Chun; Jiang, Nan
Abstract : Next‐Generation Biodegradable Vascular Stents In article number 2210053, Nan Jiang, Chun Tang, Yong Yang, Peiling Ke, and co‐workers report the self‐healing in silicon nanowires. A recovery of fracture strength (10.1%) on fractured silicon nanowires is achieved, which is demonstrated by in situ transmission electron microscopy tensile tests. The self‐healing mechanism and factors governing the self‐healing efficiency are revealed by a combination of atomic‐resolution characterizations and atomistic simulations.